Interpersonal communication - West, Richard L.; Turner, Lynn H. (Sage Publications, 2023)
With its unique skill-building approach, Interpersonal Communication Fifth Edition provides students with the knowledge and practice they need to make effective choices as communicators in today′s rapidly changing, technologically-advanced, and diverse society. Rather than "telling" students how to communicate, authors Richard L. West and Lynn H. Turner integrate skill sets in each chapter so students can apply what they learn to their own lives. Rich with current examples and coverage of technology, social media, and diversity, this practical text makes clear connections among theory, skills, and the situations we all encounter on a daily basis. -- Provided by publisher.